1983
DOI: 10.2134/agronj1983.00021962007500040004x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cool‐Season Perennial Grasses in Pure Stands and in Mixtures with Legumes1

Abstract: Clarification of relationships among species in mixed stands is essential to enlightened management of forage mixtures. During 1976–1979, we evaluated several grass‐legume mixtures in a field study in eastern Kansas. Grasses were: commercial smooth brome, Bromus inermis Leyss.; ‘Regar’ Turkish brome, B. biebersteinii Roem. &Schult.; ‘Kentucky 31’ tall fescue, Festuca arundinacea Scbreb.; and ‘Ioreed’ reed canarygrass, Phalaris arundinacea L. Legumes were: ‘Kanza’ alfalfa, Medicago sativa L.; ‘Kenstar’ red clov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
36
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 3 publications
10
36
1
Order By: Relevance
“…This result is in agreement with other studies (Carter and Scholl, 1962;Barnett and Posler, 1983;Jones et al, 1988). This result is in agreement with other studies (Carter and Scholl, 1962;Barnett and Posler, 1983;Jones et al, 1988).…”
Section: Herbage Accumulationsupporting
confidence: 94%
See 1 more Smart Citation
“…This result is in agreement with other studies (Carter and Scholl, 1962;Barnett and Posler, 1983;Jones et al, 1988). This result is in agreement with other studies (Carter and Scholl, 1962;Barnett and Posler, 1983;Jones et al, 1988).…”
Section: Herbage Accumulationsupporting
confidence: 94%
“…One benefit includes better forage nutritive value for cattle compared with grass monoculture (Barnett and Posler, 1983;Sleugh et al, 2000). One benefit includes better forage nutritive value for cattle compared with grass monoculture (Barnett and Posler, 1983;Sleugh et al, 2000).…”
Section: Evaluation Of Alfalfa-tall Fescue Mixtures Across Multiple Ementioning
confidence: 99%
“…Schmidt (1993) has reported that the quality of forages could be altered owing to differences in temperature and precipitation. Previous studies have shown that alfalfa contains significantly more crude protein than grasses and that grass + legume mixtures contain more crude protein than do the pure sowing grasses (Barnett and Posler, 1983;Höflich et al, 1990;Spandl and Hesterman, 1997;Albayrak and Ekiz, 2005). Other important quality parameters for forages are the concentrations of ADF and NDF (Caballero et al, 1995;Assefa and Ledin, 2001 NDF than the grasses grown in monoculture (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Results of a pan-European experiment, which included a Canadian site, have demonstrated that mixing grasses and legumes increases dry matter (DM) yield (Finn et al 2013) with no negative effects on nutritive value (Sturludóttir et al 2013). Adding a legume into a grass sward has been shown to increase forage DM yield and crude protein concentration (Barnett and Posler 1983) and improve forage nutritive value (Papadopoulos et al 2001). Furthermore, mixing timothy (Phleum pratense L.) with alfalfa (Medicago sativa L.) has been shown to increase the non-structural carbohydrate concentration of forages (Bélanger et al 2014), potentially resulting in a more efficient use of nitrogen (N) by ruminants (Brito et al 2009).…”
Section: Introductionmentioning
confidence: 99%